Diversity of endophytic microorganisms of plants of Kazakhstan and their biological features (Eurasian Journal of Ecology, 2021)
The article presents data on the isolation of endophytic microorganisms from 7 medicinal plants (Achillea millefolium, Artemisia laciniata, Xanthium strumarium, Medicago sativa, Cloverus officinalis and Salvia deserta) at the territory of Almaty region. The genus determination of bacteria and actinobacteria was carried out by studying the morphological, physiological and biochemical properties. From various medicinal plants, 94 different bacterial isolates were isolated. It was shown that the maximum number of endophytic bacteria was isolated from plants of Fabaceaefamily. Differences in the distribution of bacteria, actinobacteria, microscopic fungi and yeasts in the composition of plants belonging to different families and species were revealed.Among the isolated isolates, 27 were classified as Gram-negative, 30 as non-spore-forming grampositive, 19 as actinobacteria, and 16 as Gram – positive spore – forming bacteria of the genus Bacillus.It is shown that the endophytic microbiota is mainly distributed in the underground part of plants, in the root. This pattern is typical for bacteria, actinobacteria, and microscopic fungi. The largest number of endophytic bacteria was isolated from plants of the species Medicago sativaof the Semirechenskaya local variety (331.8 ± 5.4 х104 CFU per 1 g of plant tissue), as well as in Cloverus officinaliswith similar results.To activate the natural potential of microorganisms, it is important to choose the right nutrient medium that can support the sustainable growth and development of endophytes, without creating favorable conditions for the life of competing microorganisms. Cultivation was carried out under aerobic conditions. Regardless of the taxonomic group of endophytes, it is necessary to use special nutrient media for their isolation and cultivation.Key words:medicinal plants, endophytic microorganisms, antagonistic and growth-stimulating activity, bacteria, nutrient media.